Factors of Formation and Study Principles of Irony - Khamdamovna, Mavlonova Ugiloy (International Journal on Integrated Education, 2023)
This article discusses the history of the development of irony in world literature, the factors of its formation, functions and place, application in various disciplines. One by one, the main approaches to the study of irony are explained. Irony has been proven as an indirect motivational tool for changing an outdated value system.